Diagnosis of Fragile X Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Direct diagnosis by DNA analysis of the fragile X syndrome was studied in 511 persons from 63 families with the syndrome at the Institute National de la Sante et de la Recherce Medicale (INSERM), Unite 184, Faculte de Medecine, Strasbourg, France and other laboratories.